Beam-profile-compensated quantum yield measurements of upconverting nanoparticles. Issue 33 (9th August 2017) - Mousavi, Monirehalsadat; Thomasson, Björn; Li, Meng; Kraft, Marco; Würth, Christian; Resch-Genger, Ute; Andersson-Engels, Stefan
Abstract : The UCNP luminescence signal depends non-linearly on the excitation power density, making beam profiling essential in quantum yield measurements. The 2D Gaussian and its squared profile illustrates this concept. Abstract : The quantum yield is a critically important parameter in the development of lanthanide-based upconverting nanoparticles (UCNPs) for use as novel contrast agents in biological imaging and optical reporters in assays. The present work focuses on the influence of the beam profile in measuring the quantum yield ( ϕ ) of nonscattering dispersions of nonlinear upconverting probes, by establishing a relation between ϕ and excitation light power density from a rate equation analysis. A resulting 60% correction in the measured ϕ due to the beam profile utilized for excitation underlines the significance of the beam profile in such measurements, and its impact when comparing results from different setups and groups across the world.